PHYSICAL EDUCATION: AN INCLUSIVE APPROACH IN BROOK SCHOOL LUIZ DE LIMA (Fiep Bulletin - online, 2014)
The Physical Education curriculum is a component that comes over time showing that it can be the difference between inclusion and exclusion. To stand before the difficulties presented in inclusive education as a way for the acceptance of differences, physical education shows that it is able to work inclusion, which contributes to the growth of the student as a person who knows their rights and fulfill their duties . The school has special role in the inclusion process. It is the starting point and the process. No school inclusion would not be possible, because it is what you learn in school citizenship, living, socializing. It can be seen then that the school is not only workup, it is also a place of discoveries and challenges. At the moment, the biggest challenge is the inclusion. When the family realizes it needs a complement to educate your child she comes to school and so, with the collaboration of the family, the school does its role in the construction of knowledge of the student. But when the family has a carrier of special educational needs within the home, believes that the school can not help, because "the patient" needs personal care. It is in this scenario that physical education stands as one of the indicators of progression in the process of knowledge construction related to the inclusion of PNEEs in classrooms. The emphasis is on adapting the teacher and not the student. See if this reality is being developed in school luiz ribeiro file is the main objective of this study.
Keywords: Inclusion; citizenship; physical education.